Equity in the utilisation of hospital inpatient services in Ireland? an improved approach to the measurement of health need - Layte, Richard (Economic & Social Studies, 2007)
The complex interweaving of public and private provision in Irish hospitals has led to concerns that hospital care is not available to all on the basis of need alone. Previous research on Irish hospitals found that utilisation was neutral across the income distribution controlling for health status ? i.e., there was essentially equal treatment for equal need irrespective of income. However, the health indicator used in these analyses may not consistently measure health status across income groups. In this paper we combine multiple indicators into a composite `Ill Health Index? and find that the measure used for standardisation has important consequences.
Keywords: Health services; Hospitals; Ireland; Health need; Inpatient services